2006
DOI: 10.1038/sj.ejcn.1602477
|View full text |Cite
|
Sign up to set email alerts
|

Additional anthropometric measures may improve the predictability of basal metabolic rate in adult subjects

Abstract: Background:The most commonly used predictive equation for basal metabolic rate (BMR) is the Schofield equation, which only uses information on body weight, age and sex to derive the prediction. However, because body composition is a key influencing factor, there will be error in calculating an individual's basal requirements based on this prediction. Objective: To investigate whether adding additional anthropometric measures to the standard measures can enhance the predictability of BMR and to cross-validate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 18 publications
4
50
1
2
Order By: Relevance
“…The error that results from using these equations to predict the mean basal metabolic rates of either children or adult groups was established in the original work as ±2.2-3.4% for groups of 10 subjects (Schofield et al, 1985). Similar accuracy for predicting group means has been subsequently reported by a number of other investigators (De Lorenzo et al, 2001;Piers et al, 1997;Johnstone et al, 2006;Rodriguez et al, 2000;van der Ploeg et al, 2001). …”
Section: Basal Versus Walking Metabolismsupporting
confidence: 83%
See 1 more Smart Citation
“…The error that results from using these equations to predict the mean basal metabolic rates of either children or adult groups was established in the original work as ±2.2-3.4% for groups of 10 subjects (Schofield et al, 1985). Similar accuracy for predicting group means has been subsequently reported by a number of other investigators (De Lorenzo et al, 2001;Piers et al, 1997;Johnstone et al, 2006;Rodriguez et al, 2000;van der Ploeg et al, 2001). …”
Section: Basal Versus Walking Metabolismsupporting
confidence: 83%
“…We used predictive equations rather than direct measurements for this purpose because doing so was necessary for the inclusion and consistent treatment of the 25 qualifying literature group data points used in our scaling analysis. The literature amply supports the ability of the population equations used to predict group means (De Loreonzo et al, 2001;Piers et al, 1997;Johnstone et al, 2006;Rodriguez et al, 2000;Schofield et al, 1985;van der Ploeg et al, 2001;Weyand et al, 2009), indicating an approximate accuracy of 3% for the group sizes assessed here. Indeed, for the six adult subjects on whom we took direct measurements, this was the accuracy observed; the mean predicted value was 3.2% greater than the measured value.…”
Section: Equivalent Speeds and Energy Expenditure In Walking Gaitssupporting
confidence: 60%
“…Comparison of results from studies in young Brazilian women using the same protocol and calorimeter showed that BMR was not significantly different between women who lived in the tropics (Niterói, Rio de Janeiro state) (3) and women who lived below the Tropic of Capricorn in the temperate (11) 5813 (27) region of the country (Porto Alegre, Rio Grande do Sul state, at 30801 0 59 00 S, 51813 0 48 00 W) (13) . The Schofield equations have also been shown to be inadequate to estimate BMR in clinical settings of people living in Europe and North America (5,7,(39)(40)(41)(42)(43) . It has been suggested that the equations have unsolved problems in origin because they were based on a non-representative sample of the population (6) , limiting their use for prediction of BMR in different populations.…”
Section: Discussionmentioning
confidence: 99%
“…An overwhelming majority (99%) of dietitians surveyed use the Schofield equation to calculate BMR. The Schofield equation does not incorporate measurements of body composition, despite its impact on BMR, which therefore limit its validity for use in individuals (Johnstone et al, 2006). The consistent use of the Schofield equation to calculate BMR is likely to be owing to its recommendation by standard clinical texts in the UK (Thomas, 2001;Todorovic and Micklewright, 2004).…”
Section: Discussionmentioning
confidence: 99%